A STUDY ON PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ANALYSIS OF METHANOLIC EXTRACT OF SPHAERANTHUS INDICUS LINN LEAVES. - Karunya Arumugam; Sathish Sankar (Chelonian Research Foundation, 2023)
Introduction: Sphaeranthus indicus Linn, commonly known as "Gorakhmundi" or "East Indian Globe Thistle," is a medicinal plant that has been traditionally used in various systems of medicine for its therapeutic properties.It belongs to the Asteraceae family and is widely distributed in India, Southeast Asia, and other tropical regions.The plant has gained attention due to its potential health benefits and is known for its diverse phytochemical composition.Phytochemical analysis plays a crucial role in identifying and quantifying the bioactive compounds present in plants. Various classes of phytochemicals, such as alkaloids,flavonoids, terpenoids, phenolic compounds, and others, are known to exhibit antioxidant properties and contribute to the plant's medicinal properties. This study aims to conduct an in vitro phytochemical analysis and evaluate the antioxidant activity of Sphaeranthus indicus Linn. Aim: To determine the Phytochemical analysis and Antioxidant activity of sphaeranthus indicus linn Materials and methods: Preparation of Methanolic Extracts by collecting the leaf samples , Qualitative Phytochemical Screening,Determination of In Vitro Antioxidant Activities of the Studied PlantExtracts by DPPH assay and hydroxyl scavenging activity,Determination of Total Phenolic Contents and Determination of Total Flavonoid Contents. Results: The antioxidant activity of Sphaeranthus indicus Linn extracts was evaluated using different assays such as DPPH radical scavenging assay, and hydroxyl radical scavenging activity assay.The plant extract showed similar antioxidant activity compared to the control ( L Ascorbic acid).The qualitative phytochemical screening of the methanolic extracts revealed the presence of various phytochemical groups in Sphaeranthus indicus Linn, including saponins, alkaloids, terpenoids, flavonoids, cardiac glycosides, steroids, and phenols. Conclusion: In conclusion, the in vitro phytochemical analysis and antioxidant activity of Sphaeranthus indicus Linn demonstrate its potential as a valuable medicinal plant. The qualitative screening revealed the presence of various phytochemical groups, including saponins, alkaloids, terpenoids, flavonoids, cardiac glycosides, steroids, and phenols .These phytochemicals contribute to the antioxidant activity of Sphaeranthus indicus Linn extracts.The observed antioxidant activity suggests that Sphaeranthus indicus Linn extracts may possess significant health benefits by protecting against oxidative stress-related diseases. Keywords: Phytochemicals , methanolic extract,universal health , diseases, well being, health, international health policy .